Comparison of control strategies for thermoelectric generator emulator - Ayop, Razman; Tan, Chee Wei; Ayob, Shahrin Md; Daud, Mohd Zaki; Jamian, Jasrul Jamani; Nordin, Norjulia Mohamad (Institute of Advanced Engineering and Science, 2023)
Thermoelectric generator (TEG) can directly convert heat energy into electrical energy. It improves the power efficiency of the energy generation system by converting the power loss in the form of heat produced during the generation process into additional electrical energy. The TEG emulator (TEGE) is a power converter that produces a similar current-voltage characteristic as the TEG. It is a valuable device used to develop and test the TEG-based energy generation system. Nonetheless, the research on the TEGE is still in the early stage. This paper proposed a proper, low-cost, and high-efficient TEGE design using the buck converter. The contribution of the paper covers the TEG model in the form of an array, the buck converter design tailored to the TEGE, and 4 new control strategies proposed for the TEGE. The control strategies are the direct referencing method (DRM), perturb and observed (PnO) method, resistance comparison method (RCM), and resistance feedback method (RFM). The conventional proportional-integral controller is used to maintain a smooth operation during transient and steady-state periods. The results show the merits or demerits for each proposed control strategy based on the accuracy, transient response, stability, overshoot, and efficiency.